Digitalisasi Pembelajaran Berbasis 3D Augmented reality Genset 2000 kVA dan Audio Visual Untuk Menunjang Pembelajaran Praktik di Prodi Teknologi Bandar Udara - Djunaedi; Khadijah; Putra Maha Surya; Anis Muhammad Rizal (Politeknik Penerbangan Makassar, 2022)
Technological developments, especially in the field of education, are becoming a special concern in various countries in the world. The Covid-19 crisis, which brought the face-to-face education system to a halt and required learning to be carried out online, had many negative impacts on cadets. Practices that should be able to help understanding cannot be realized because they are online, so an effective method is needed as a substitute for cadet practice at the Makassar Aviation Polytechnic. Products designed by researchers can show the effectiveness of virtual 3D augmented reality and audiovisuals have been seen from the learning outcomes of cadets, and the responses of cadets after using the application. Making learning applications based on virtual 3D augmented reality and audio-visual 2000 kVA generators are expected to be a solution for distance learning practices. Where 3D images can be seen more clearly from various sides making it easier for cadets to imagine. Coupled with audiovisuals that provide interesting explanations when the 3D design is used. In addition, learning applications also make it easier for cadets to be able to learn anytime and anywhere in a more structured manner.